Notes on new and old world African drumming: just playing it like you mean it is not playing - Coplan, David B. (International Library of African Music, 2017)
Certainly the most lasting impression I brought home from my "hippie summer" of 1968 in Berkeley, California was of those fierce conga drum ensembles that gathered almost daily in lower Sproul Plaza. Then, as now, there was great variation in the quality of the playing. On one set of benches sat a motley crew of drum thumpers, banging away without Time; sound and fury signifying egotism and indiscipline. At a deliberate distance sat another ensemble, three or four dignified black men well past adolescence in every sense, the conga (golpe) melody drum and the lead or quinto placed properly on either side of the bass (tumbao). Their rhythms were complex yet clearly articulated, restrained yet thoroughly compelling, relentlessly goading the body and spirit into dance.
Keywords: African Music